2002
DOI: 10.1097/00129492-200209000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Implant Part II: Subjective Assessment of Functional Outcome

Abstract: It was concluded that the auditory brainstem implant is an effective support for receiving and, to some degree, differentiating environmental sounds, and that as an adjuvant to lip-reading, it enhances speech perception, especially in quiet surroundings. A comparison between the results of this study and the results of the audiologic tests presented in Part I of this study (published earlier) revealed that patient satisfaction was not directly correlated with the results of the objective auditory tests. In gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 5 publications
2
24
0
2
Order By: Relevance
“…Their word identification scores changed due to their chronological age, duration of ABI use, and cognitive development. Results of speech recognition skills are also similar to those of other studies [14,[16][17][18][19] . Open-set sentence recognition is improved in 12 of the children.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Their word identification scores changed due to their chronological age, duration of ABI use, and cognitive development. Results of speech recognition skills are also similar to those of other studies [14,[16][17][18][19] . Open-set sentence recognition is improved in 12 of the children.…”
Section: Discussionsupporting
confidence: 88%
“…All children used their ABI regularly on a daily basis, and similar to the findings in the literature, they were found to develop awareness toward environmental sounds and speech sounds after 1-month to 3-month intervals [11][12][13][14] . Functionality of auditory perception skills was mostly evaluated with MAIS/IT-MAIS in researches; however, in our research, FAPCI was conducted to determine auditory functioning and compared with normally hearing population.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our sample, the presence of hearing thresholds corresponding to mild hearing loss and even normal thresholds in some frequencies suggest the patients were able to perceive many sounds in the environment, including high frequencies, showing that the ability to perceive environment sounds and perform speech recognition assisted by lip reading can be restored with this type of implant 8,9 . Although the outcomes provided by the auditory brainstem implants were compared against those of one-channel cochlear implants 10 , the early free field audiometry test results were positively surprising, mainly in terms of patient compliance and daily use of the hearing aid.…”
Section: Discussionmentioning
confidence: 99%
“…Functional results show great variability; from noise perception only to useful speech discrimination in audiovisual mode in a few patients so far. Since the early trials by Hitselberger and House in 1979, as reported by Edgerton et al 13 and Hit sel berger et al, 21 profound improvements in implant array, technology, and speech processing strategies 65 have brought about useful improvement in functional outcome, 4,8,9,17,23,29,31,32,37,42,43,45,46,48,58,59 but still results remain less favorable than in cochlear implants or auditory brainstem implants (ABIs) in patients without NF2. 8 Visionindependent speech perception is not generally achieved.…”
mentioning
confidence: 99%